A nontoxic and low-cost hydrothermal route for synthesis of hierarchical Cu(2)ZnSnS(4) particles - Xia, Yu (Springer, 2014)
We explore a facile and nontoxic hydrothermal route for synthesis of a Cu(2)ZnSnS(4) nanocrystalline material by using l-cysteine as the sulfur source and ethylenediaminetetraacetic acid (EDTA) as the complexing agent. The effects of the amount of EDTA, the mole ratio of the three metal ions, and the hydrothermal temperature and time on the phase composition of the obtained product have been systematically investigated. The addition of EDTA and an excessive dose of ZnCl(2) in the hydrothermal reaction system favor the generation of kesterite Cu(2)ZnSnS(4). Pure kesterite Cu(2)ZnSnS(4) has been synthesized at 180°C for 12 h from the reaction system containing 2 mmol of EDTA at 2:2:1 of Cu/Zn/Sn. It is confirmed by Raman spectroscopy that those binary and ternary phases are absent in the kesterite Cu(2)ZnSnS(4) product. The kesterite Cu(2)ZnSnS(4) material synthesized by the hydrothermal process consists of flower-like particles with 250 to 400 nm in size. It is revealed that the flower-like particles are assembled from single-crystal Cu(2)ZnSnS(4) nanoflakes with ca. 20 nm in size. The band gap of the Cu(2)ZnSnS(4) nanocrystalline material is estimated to be 1.55 eV. The films fabricated from the hierarchical Cu(2)ZnSnS(4) particles exhibit fast photocurrent responses under intermittent visible-light irradiation, implying that they show potentials for use in solar cells and photocatalysis.